2022
DOI: 10.15244/pjoes/146936
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Potential Geographic Distribution of Endangered Relict Tree Species <i>Dipteronia sinensis</i> in China Based on MaxEnt and GIS

Abstract: Dipteronia sinensis is an endangered relict tree species in the endemic north temperate flora of China, which has important reference values for studying paleoclimate and species variation as well as geographic zonation changes. Based on 96 occurrence points of D. sinensis and 9 environmental factors, the potential geographic distribution of D. sinensis in China under climate change was predicted using MaxEnt model and ArcGIS software, the Jackknife test was used to assess the important factors governing its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…In this analysis, when the presence probability exceeded 0.5, it indicated that the corresponding environmental factor value favoured the growth of S . italica [ 12 ]. To provide a more intuitive description of the influence of environmental variables on the distribution of S .…”
Section: Resultsmentioning
confidence: 99%
“…In this analysis, when the presence probability exceeded 0.5, it indicated that the corresponding environmental factor value favoured the growth of S . italica [ 12 ]. To provide a more intuitive description of the influence of environmental variables on the distribution of S .…”
Section: Resultsmentioning
confidence: 99%
“…Temperature regulates plant metabolic rates, which are critical for plant survival, growth, and reproduction. The variation range of temperature was closely related to the large-scale landscape geographical distribution of plant species [27,28]. The elevation is also a second important factor in the distribution of D. oxleyanus, with a percent contribution and permutation importance of 16.1% and 13%, respectively, and the habitat suitability at elevation was 400-800 m asl.…”
Section: Potential Distribution Areas Of D Oxleyanus In Sumatramentioning
confidence: 94%
“…According to Li et al [17], the ecological niche of Paeonia delavayi may also be affected by rapid changes in temperature and precipitation in the context of global climate change. Liu et al [36] used the Maxent model to simulate the response of Paeonia delavayi to climate change, showing that the area and elevation of the plant's range would change with increasing temperature, and the plant's response to climate change was simulated by Liu et al Huang et al [1] explored the potential habitat of Dipteronia sinensis and showed that the suitable distribution areas of plants are strongly influenced by climatic variables such as temperature and precipitation and will change with changes in these variables, with some habitat areas disappearing and some new habitat areas emerging. Yang et al [37] showed that temperature, precipitation, and their variation are the main environmental factors governing Xikang Yucca, further illustrating the study's accuracy.…”
Section: Changes In the Potential Geographical Distribution Of Paeoni...mentioning
confidence: 99%
“…Among the top ten environmental problems in the world, climate change is listed as the most important issue. In the context of global climate change, the response and feedback of food crops to climate change have become one of the core research areas and focal issues [1]. Climate change irreversibly changes the ecosystem and ecological environment on which species depend.…”
Section: Introductionmentioning
confidence: 99%